Suid-Afrikaanse fundamentele regte as ’n determinant vir die onderwys - ’n oorsig - Oosthuizen, Izak (Koers, 1995)
South African fundamental rights as a determinant of education. The changing scene in South African education is responsible for uncertainty among the participants in South African education. As one of the main functions of law is to create order, the application of certain legal determinants to South African education could contribute to regularity in education. This article focuses on the regulating role of the Bill of Fundamental Rights in the Constitution of the Republic of South Africa within the local education situation. In particular, the influence it has on the position of three of the major elements in teaching - the school, the pupil and the teacher - is considered. Not only are the ethos and nature of the school influenced by the Bill of Fundamental Rights, but the Bill also creates a framework fo r equality, democracy and freedom within the school. The pupil and the teacher are protected in certain ways against the abuse ofpower by the bearer of authority, the state.